Time‐iteration‐domain integrated learning control for robust trajectory tracking and disturbance rejection: With application to a PMLSM. Issue 18 (21st September 2021) - Liu, Weike; Xu, Yunlang; Ding, Runze; Shu, Feng; Yang, Xiaofeng
Abstract: Iterative learning control (ILC) has been widely used to improve motion performance when reference trajectories and external disturbances are strictly repetitive. However, the occurrence of non‐repetitive trajectories and disturbances would significantly deteriorate the performance of traditional ILC methods. To solve this problem, a time‐iteration‐domain integrated learning control (TIDLC) scheme is proposed for enhancing robustness against non‐repetitive trajectories and disturbances. The TIDLC scheme consists of an ILC term and a time‐domain compensator (TC) term. While the ILC term that performs learning in the iteration‐domain preserves excellent performance under repetitive tasks, the TC term that is updated in the time‐domain can compensate for the variations of trajectories and disturbances. Stability and performance analyses are discussed in both the time‐domain and iteration‐domain. Experimental results on a permanent magnet linear synchronous motor (PMLSM) positioning system verify the validity of the proposed scheme.